Managing the implementation of e-government in Malaysia: a case of E-Syariah - Muhammad, Muhd. Rosydi (INSI Publications, 2013)
Governments worldwide are increasingly engaged in the national e-government initiative as it is perceived to be an enabler for the improved transparency, efficiency and effectiveness of services delivered to citizens and businesses. Failure of the governments to fulfill basic requirements and perform its duties in supporting the initiative has been coined as one of the factors that hinder e-government to accomplish the promise of a more transparent, efficient and effective public service delivery. Thus, this exploratory research aims at understanding on the strategic key implementation tasks of government in managing the successful e-government implementation, particularly in Malaysia. Case study approach was adopted by the means of semi-structured interviews with 14 of the Malaysian public sector officials responsible for the implementation of E-Syariah. Results from the empirical case data confirm the existing six government’s key implementation tasks as discussed in the literature, and two key tasks emerged from the case study – inculcating sacred value and awareness, and instilling ICT value among staff. This provides governments with a good insight of basic managerial responsibilities in deploying e-government projects. Further, the identified key tasks can be the focal point for government officials to consider in their efforts to support successful implementation of e-government.